2020
DOI: 10.2147/cmar.s250093
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiRNA-128 and MiRNA-142 Regulate Tumorigenesis and EMT in Oral Squamous Cell Carcinoma Through HOXA10</p>

Abstract: Background: Oral squamous cell carcinoma (OSCC) accounts for more than 90% of all oral cavity cancers, and the 5-year survival rate for OSCC patients remains unsatisfactory. MiRNA-128/miRNA-142 has been reported to work as a tumor suppressor in diverse tumors. However, the biological function of miR-128/miR-142 in OSCC is still unknown. Methods: The expression of miR-128/miR-142 and homeobox A10 (HOXA10) in OSCC tissues and cells was measured by quantitative real-time polymerase chain reaction (RT-qPCR). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…miR-128 is known to affect tumorigenesis in a number of cancer types [ 28 ] and has been suggested to play various regulatory roles in the central nervous system [ 29 , 30 ], but no reports are available linking it to the pathogenesis or prognosis of Wilms’ tumor. The overexpression we initially observed in Patient 1 was not reproducible across all samples, with some showing an elevation and others a decrease ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-128 is known to affect tumorigenesis in a number of cancer types [ 28 ] and has been suggested to play various regulatory roles in the central nervous system [ 29 , 30 ], but no reports are available linking it to the pathogenesis or prognosis of Wilms’ tumor. The overexpression we initially observed in Patient 1 was not reproducible across all samples, with some showing an elevation and others a decrease ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was previously reported that miR-770 could promote the migration and invasion of OSCC cells by regulating the NAD-dependent protein deacetylase sirtuin-7 (Sirt7)/Smad4 pathway ( 17 ). Moreover, miR-128 and miR-142 could regulate the tumorigenesis and epithelial-mesenchymal transition in OSCC through mediation of homeobox protein Hox-A10 ( 18 ). Meanwhile, Luo et al ( 19 ) found that miR-149-5p could regulate cisplatin chemosensitivity, cell growth, and metastasis of OSCC cells by targeting TGFβ2.…”
Section: Introductionmentioning
confidence: 99%
“…Different from deregulation of mRNA expression levels, miRNA expression alterations are mostly due to promoter-related changes 1,57,58 . The role of miRNA deregulation in oral cancer have been explored in several studies, therein, presenting compelling evidence for the involvement of miRNAs in angiogenesis, tumor progression, invasion, etc [58][59][60] . However, the regulatory mechanisms behind miRNA expression deregulation at a genome scale remained largely unknown.…”
Section: Discussionmentioning
confidence: 99%